Effects of thymosin β4-derived peptides on migration and invasion of ovarian cancer cells - Yoon, Hyung Joon; Oh, Young Lim; Ko, Eun-Ji; Kang, Ahyun; Eo, Wan Kyu; Kim, Ki Hyung; Lee, Ji Young; Kim, Ari; Chun, Sungwook; Kim, Hongbae; Ock, Mee Sun; Cha, Hee-Jae (Genes & genomics, 2021)
Background Thymosin β4 (Tβ4) is a highly conserved actin binding protein associated with the metastatic potential of tumor cells by stimulating cell migration. The role of Tβ4 and its derived fragment peptides in migration of ovarian cancer cells has not been studied. Objective To analyze the effects of Tβ4 and its derived fragment peptides on ovarian cancer cell migration and invasion, we applied Tβ4 and three Tβ4-derived synthetic peptides to SKOV3 ovarian cancer cells. Method The migration and invasion of SKOV3 cells treated with Tβ4(1–43), Tβ4(1–15), Tβ4(12–26), Tβ4(23–), and untreated control were analyzed by in vitro migration and invasion assay with transwell plate. Cell proliferation assay was conducted to identify the effect of Tβ4 and its derived peptide on SKOV3 cell proliferation. The expression of Tβ4 related proteins related with cell proliferation was analyzed by Western blot after treatment with Tβ4 and its derived peptides. Results Cell migration and invasion were significantly increased in Tβ4 peptide-treated SKOV3 cells compared with untreated control. All three Tβ4-derived fragment peptides including those without an actin binding site significantly stimulated migration and invasion of SKOV3 cells. Tβ4 and its derived peptide significantly stimulated SKOV3 cell proliferation and up-regulated the expression of RACK-1 protein. Conclusions The Tβ4 peptide and all of its derived fragment peptides including those without an actin binding motif stimulate migration and invasion of SKOV3 ovarian cancer cells. All peptides significantly increased RACK-1 expression and cell proliferation of SKOV3 cells. These results suggest that Tβ4 stimulates migration and invasion of SKOV3 cells by stimulation of cell proliferation through up-regulation of RACK-1 protein.